Simulated Ocean Circulation from INDESO data in the Region of the Gulf of Tomini - Satria Yukiadi Santoso; Agus Saleh Atmadipoera; I Wayan Nurjaya; Dwiyoga Nugroho; Ariane Koch-Larrouy (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2022)
The Tomini is one of the largest gulf in Indonesia. The gulf also has a unique profile and adjacent to Maluku Sea which is the eastern route of the Indonesian Throughflow. The purpose of this research is to investigate and analyze the circulation patterns that occur inside the gulf of Tomini and Maluku Sea as well as the variability of physical parameters such as temperature, salinity and transport volume and to correlate the driving factors of ocean-atmosphere phenomena that affect these physical parameters using the INDESO model dataset from January 2008 to December 2014 (7 years). The results showed that the surface circulation in the gulf and Maluku Sea flows southeastward to the Lifamatola Strait during the northwest and 1st transition, during the southeastern season the circulation flows leaving Maluku Sea through the ITF entry to the Pacific and Sulawesi Seas, and then flows southeastward during 2nd transition. The seawater temperature in the study area ranges between 28.6 - 32.0°C and the salinity varies between 32.2-34.4 psu. Vertical structure of zonal current in the gulf reveals velocity range from 0.02-0.3 Sv and the surface layer current is dominated by the westward flow, while at 20-60 m depth the flow is eastward. The mean transport volume at transects 123°E is about -0.028 (±0.2578) Sv. Variability of transport volume revealed spatial anomalies and periodicity on the intra-seasonal, semi-annual, annual, and inter-annual time-scales. Those are significantly coherence with zonal and meridional winds forcing in the Indo-Pacific region.